Day of the Week Effect Anomaly and Efficiency: A Recent Study on Indian Stock Market: The absence of the 'Day of the Week Effect' anomaly and the weak form of efficiency in the Indian stock market (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper attempts to investigate the “Day of the week effect” anomaly in Indian stock market. As the stock market is more efficient, the chances of occurring different market anomalies would be less. So it is also tried out to check at least the weak form of efficiency of Indian stock market. NSE Nifty is a leading market performance indicator, so daily closing value of Nifty is collected between the year 2009 and 2018. Under different parametric tests, it is found that “Day of the week effect” anomaly is not found in Indian stock market and the market shows the Weak form of Efficiency. This result is opposite to the previous findings in respect to Indian market.